ENGLISH STUDY CLUB: HOW STUDENTS' MENTAL ATTRIBUTES REFLECT THEIR MOTIVATION - Siti Maria Ulfa Mattarima; Nur Afifi; Rezki Suci Qamaria (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2022)
This study focuses on investigating the main motivation of students in theEnglish club and testing the level of motivation based on the aspects oflearning motivation that have been developed by Worell and Stilwell. Thisstudy aims to reveal the difference in motivation between on-campusclubs and English clubs using quantitative descriptive methods on thesubjects of students in the second semester to the final semester of theEnglish Department. The data was collected through a questionnaire andanalyzed using a non-parametric test, Mann-Whitney. This study indicatesno significant difference between student learning motivation on campusand the English Club from the average of six aspects of learningmotivation. However, the English club was superior in terms of feedbackand goals as the primary motivation for students. From these results, it isknown that the English club contributes well to the mental attributes ofstudents in practicing English proficiency.